2016
DOI: 10.1055/s-0036-1593754
|View full text |Cite
|
Sign up to set email alerts
|

Complication of Community-Acquired Pneumonia (Including Cardiac Complications)

Abstract: Community-acquired pneumonia (CAP) represents an important public health problem and carries significant morbidity, mortality, and costs. The incidence of CAP is highest among children and elderly patients, but the mortality is much higher in patients older than 65 years. Despite the advances in medicine, the administration of antimicrobials, and the overall better care, there are still patients with CAP dying due to systemic complications all over the world. A continuum of CAP disease progression may involve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 64 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that underlying conditions such as renal, cardiovascular diseases and diabetes mellitus increase the risk and severity of CAP in individuals. 1,25 This may serve as a prognostic factor for the physicians to make better decisions on the diagnosis and overall patient management. 2 Although this study does not show any statistical difference between the presence of M. pneumoniae and underlying diseases (p value >0.05), the odds ratio of MPP were 1.99, 1.80 and 0.7 in kidney disease, diabetes and cardiovascular disease respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that underlying conditions such as renal, cardiovascular diseases and diabetes mellitus increase the risk and severity of CAP in individuals. 1,25 This may serve as a prognostic factor for the physicians to make better decisions on the diagnosis and overall patient management. 2 Although this study does not show any statistical difference between the presence of M. pneumoniae and underlying diseases (p value >0.05), the odds ratio of MPP were 1.99, 1.80 and 0.7 in kidney disease, diabetes and cardiovascular disease respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Important systemic complications related to pneumonia include direct progression of the disease in the lungs to involve the pleural space or indirect effects on other organ systems such as the central nervous system, hematological, cardiac, renal, endocrine, and/or hepatic systems, and others ( 69 – 71 ). Workshop participants emphasized the concept that pneumonia is not a disease solely confined to the lung parenchyma but should be considered to be a systemic disease leading to organ dysfunction with impacts on short-term and long-term outcomes.…”
Section: Host Clinical Consequences Of Pneumoniamentioning
confidence: 99%
“…It is now well recognized that cardiovascular events (CVEs) represent one of the most important and frequent complications of CAP, occurring in up to 30% of cases and associated with significant mortality [ 20 , 41 ]. Among the common cardiac complications are acute myocardial infarction, new or worsening arrhythmia (most commonly atrial fibrillation) and new or worsening cardiac failure.…”
Section: Cardiac Complications Of Capmentioning
confidence: 99%